The contribution of N2O3 to the cytotoxicity of the nitric oxide donor DETA/NO: an emerging role for S-nitrosylation. Issue 2 (28th March 2013) - Ali, Ahlam A.; Coulter, Jonathan A.; Ogle, Claire H.; Migaud, Marie M.; Hirst, David G.; Robson, Tracy; McCarthy, Helen O.
Abstract : The relationship between the biological activity of NO and its chemistry is complex. The objectives of this study were to investigate the influence of oxygen tension on the cytotoxicity of the NO donor DETA/NO and to determine the effects of oxygen tension on the key RNS (reactive nitrogen species) responsible for any subsequent toxicity. The findings presented in this study indicate that the DETA/NO-mediated cytotoxic effects were enhanced under hypoxic conditions. Further investigations revealed that neither ONOO − (peroxynitrite) nor nitroxyl was generated. Fluorimetric analysis in the presence of scavengers suggest for the first time that another RNS, dinitrogen trioxide may be responsible for the cytotoxicity with DETA/NO. Results showed destabilization of HIF (hypoxia inducible factor)-1α and depletion of GSH levels following the treatment with DETA/NO under hypoxia, which renders cells more susceptible to DETA/NO cytotoxicity, and could account for another mechanism of DETA/NO cytotoxicity under hypoxia. In addition, there was significant accumulation of nuclear p53, which showed that p53 itself might be a target for S-nitrosylation following the treatment with DETA/NO. Both the intrinsic apoptotic pathway and the Fas extrinsic apoptotic pathway were also activated. Finally, GAPDH (glyceraldehyde-3-phosphate dehydrogenase) is another important S-nitrosylated protein that may possibly play a key role in DETA/NO-mediated apoptosis and cytotoxicity. Therefore this study elucidates further mechanisms of DETA/NO mediated cytotoxicity with respect to S-nitrosylation that is emerging as a key player in the signalling and detection of DETA/NO-modified proteins in the tumour microenvironment.